Nanoscale Bioceramics In Bone Tissue Engineering- An Overview - Alidadi, Soodeh (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This review presents a general view on application of nanomaterials in the field of animal production and medicine especially of  nanoceramics in bone tissue engineering and regenerative medicine (TERM). Nanotechnology as an emerging field provides new and  better tools and technologies to biology, chemistry, engineering, and medicine for various applications. It has been widely employed in  poultry and animal production, food safety, as well as diagnosis and treatment of animal and human diseases. Nanomaterials including  nanoscale bioceramics are used to diagnose and treat diseases in the field of nanomedicine. TERM is continually attempting to find a  reliable and efficient method to regenerate and heal tissue defects and bone defects in particular. Due to appropriate surface features  and superior biomechanical properties to biopolymers, nanoscale bioceramics have gained more attention in bone tissue engineering.  These nanomaterials provide many advantages that are essential for bone regeneration including high bioactivity, biocompatibility,  biodegradability, suitable biomechanical strength, osteoconductivity, and osteoinductivity. However, some concerns such as cytotoxicity  potentials are associated with nanomaterials.
Keywords: Bone tissue engineering; Nanocomposites; Nanomedicine; Nanoscale bioceramic; Nanotechnalogy